Preparation and Properties of Phenol Formaldehyde Poly(Vinyl Alcohol)Resin as Fibre-Reinforced Film Adhesive - Lim, Chee Siong (2004)
This study aims to evaluate the chemical composition, physical and mechanical properties of fibre-reinforced composite via synthesis of resole fibre-reinforced phenolic resin binded and cured under heat and pressure to the outside metal faces. Two types of resin; phenol formaldehyde resin and poly(vinyl alcohol) resin were blended and applied on the paper’s surfaces (MG Craft Paper GSM: 50 Ribbed) and then arranged in an alternate manner for the adhesion of both surfaces resin.